2015
DOI: 10.1093/mnras/stv2358
|View full text |Cite
|
Sign up to set email alerts
|

Deep Chandra observation and numerical studies of the nearest cluster cold front in the sky

Abstract: We present the results of a very deep (500 ks) Chandra observation, along with tailored numerical simulations, of the nearest, best resolved cluster cold front in the sky, which lies 90 kpc (19 ) to the northwest of M 87. The northern part of the front appears the sharpest, with a width smaller than 2.5 kpc (1.5 Coulomb mean free paths; at 99 per cent confidence). Everywhere along the front, the temperature discontinuity is narrower than 4-8 kpc and the metallicity gradient is narrower than 6 kpc, indicating t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
58
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 48 publications
12
58
2
1
Order By: Relevance
“…The dominance of isothermal fluctuations of these scales in this region is consistent with the presence of several bubbles (see, e.g., Owen et al 2000;Forman et al 2007). In addition to these bubbles, at distances of about 6 7 from the center the gas is likely disturbed by largescale sloshing (e.g., Figure 2 in Simionescu et al 2010;Werner et al 2016). The most prominent cold front presumably associated with sloshing is located ∼20′ north of M87.…”
Section: Outer Regionmentioning
confidence: 99%
“…The dominance of isothermal fluctuations of these scales in this region is consistent with the presence of several bubbles (see, e.g., Owen et al 2000;Forman et al 2007). In addition to these bubbles, at distances of about 6 7 from the center the gas is likely disturbed by largescale sloshing (e.g., Figure 2 in Simionescu et al 2010;Werner et al 2016). The most prominent cold front presumably associated with sloshing is located ∼20′ north of M87.…”
Section: Outer Regionmentioning
confidence: 99%
“…XMM-Newton EPIC/MOS mosaic image of the central r ∼ 150 kpc region of the Virgo cluster (Simionescu et al 2010). The white square indicates the Chandra ACIS-I pointing of Werner et al (2016) shown in figure 6. Reproduced from Werner et al (2016).…”
Section: A3667mentioning
confidence: 99%
“…The white square indicates the Chandra ACIS-I pointing of Werner et al (2016) shown in figure 6. Reproduced from Werner et al (2016).…”
Section: A3667mentioning
confidence: 99%
“…Often the variation of this width is very subtle, and not obvious from the raw Chandra images, instead requiring a lengthy process of dividing the edge into numerous sectors, measuring surface brightness profiles across each sector, and fitting the profiles with a model (e.g. Werner et al 2016, Sanders et al 2016a.…”
Section: A2319 and A3667mentioning
confidence: 99%
“…Markevitch et al 2002, Russell et al 2012, and cavities in the intracluster medium (ICM) resulting from powerful AGN feedback (Boehringer et al 1993, McNamara et al 2000, Fabian et al 2006) leave a myriad of such surface brightness features in X-ray images. Galaxy clusters also feature X-ray surface brightness features which are much more subtle, such as sound waves (Fabian et al 2006) and substructure behind cold fronts (Werner et al 2016, Sanders et al 2016a, with Email: swalker@ast.cam.ac.uk variations of only a few percent. Our ability to unravel the physics of the intracluster medium is limited by our ability to resolve features which have low contrast in X-ray images.…”
Section: Introductionmentioning
confidence: 99%